Application of Naghom Al-Quran in Learning Recitations at the Tarbiyatul Wildan Islamic Boarding School in Subang - Muhamad Zamzam Mubarok; Lina Marlina (Penerbit Hellow Pustaka, 2025)
This study aims to examine and describe in depth the implementation of nagham (melodic patterns) of the Qur'an in the tilawah (recitation) learning process at Pondok Pesantren Tarbiyatul Wildan, Subang. Nagham, as the art of reciting the Qur'an with specific melodic tones, not only beautifies the recitation but also helps deepen the understanding of the verses and enhances students’ memorization abilities. This research employs a descriptive qualitative field method with data collected through interviews, observation, and documentation. The findings show that the learning of nagham is carried out gradually and in a structured manner using methods such as simā’i (listening directly to the teacher), talaqqi, and supervised independent practice. The types of nagham taught include Bayyati, Hijaz, Nahawand, Sikka, Soba, and Jiharkah. Students show significant progress in terms of voice quality, melody accuracy, and emotional expression in their recitations. The main obstacles encountered include the lack of vocal talent in some students, reluctance to try when prompted by instructors, and insufficient individual practice time. This study recommends that students continue practicing by adding extra practice schedules and encourages the pesantren to actively participate in LPTQ (Institute for the Development of Qur’anic Recitation) management to further develop students' potential to higher levels.